Mechanisms underlying resistance of Euschistus heros (Hemiptera: Pentatomidae) to the neonicotinoid thiamethoxam and the pyrethroid lambda-cyhalothrin - Lira, Ewerton da Costa (2024)
The increase in insecticide resistance represents a significant challenge to effective pest management, with implications for agricultural productivity. To mitigate this issue, it is essential to understand the mechanisms likely employed by which key pests survive exposure to insecticides and consequently promote the selection of resistant populations. For this reason, in this study we used RNA and DNA sequencing techniques to investigate the molecular mechanisms associated with the resistance of E. heros to thiamethoxam and lambda-cyhalothrin. Furthermore, we explored the potential contribution of the associated microbiota in this resistance phenomenon. Comparative gene expression analysis between the susceptible (SUS) and thiamethoxam-resistant (NEO) strains identified 215 significantly differentially expressed (DE) transcripts. DE transcripts associated with the metabolism of xenobiotics were all up-regulated in the NEO strain. The comparative analysis of the SUS and lambda-cyhalothrin-resistant (PYR) strains identified 204 DE transcripts, including an esterase (esterase FE4), a glutathione-S-transferase, an ABC transporter (ABCC1), and aquaporins that were up-regulated in the PYR strain. We identified 9,588 and 15,043 non-synonymous SNPs in the PYR and NEO strains in comparison with their respective SUS strains. One of the variants (D70N) detected in the NEO strain occurs in a subunit (α5) of the nicotinic acetylcholine receptor, the target-site of neonicotinoid insecticides. Nevertheless, this residue was not conserved among the α5 subunits of insect species, and may have little, if any, effect on NEO resistance. The gut microbiota analysis of E. heros revealed a strong predominance of y-Proteobacteria (Pseudomonadota), which plays a key role in the insect gut environment. The most abundant genera were from the (Enterobacteriaceae (Genus_NA_ Enterobac_ASV0008, Serratia e Yokenella) and Erwiniaceae (Genus_NA_Erwin_ASV0001, Erwinia and Pantoea). A higher microbial diversity was found in laboratory strains compared to field populations. Lambda-cyhalothrin-resistant strain (RESPYR) showed a greater abundance of Serratia, Siccibacter and Pantoea, and the Serratia and Siccibacter was also identified as potential biomarkers for lambda-cyhalothrin-resistant strains. The selection of E. heros for resistance to thiamethoxam (RESNEO) did not affect the gut microbiota diversity and the homeostasis of the community when compared to the reference susceptible strain (SUSNEO), but Yokenella was identified as potential biomarker for thiamethoxam-resistant strain (RESNEO). Comparative genomic analyses of two culturable insecticide-degrading bacteria isolated from E. heros led to the identification of the new species Serratia toxivorans n. sp. and of Delftia acidovorans. In conclusion, neonicotinoid and pyrethroid resistance in laboratory-selected strains of E. heros is associated with a potential metabolic resistance mechanism mediated by the overexpression of several proteins commonly involved in the three phases of xenobiotic metabolism. Our results also emphasize the importance of gut microbiota in metabolizing toxic compounds. Altogether, our data provides insights into the potential basis of resistance in E. heros and contributes to the development and implementation of resistance management strategies for this important insect pest.